An explanation for the mysterious distribution of melanin in human skin: a rare example of asymmetric (melanin) organelle distribution during mitosis of basal layer progenitor keratinocytes. (1st November 2018) - Joly‐Tonetti, N.; Wibawa, J.I.D.; Bell, M.; Tobin, D.J.
Summary: Background: Melanin is synthesized by melanocytes in the basal layer of the epidermis. When transferred to surrounding keratinocytes melanin is the key ultraviolet radiation‐protective biopolymer responsible for skin pigmentation. Most melanin is observable in the proliferative basal layer of the epidermis and only sparsely distributed in the stratifying/differentiating epidermis. The latter has been explained as 'melanin degradation' in suprabasal layers. Objectives: To re‐evaluate the currently accepted basis for melanin distribution in human epidermis and to discover whether this pattern is altered after a regenerative stimulus. Methods: Normal epidermis of adult human skin, at rest and after tape‐stripping, was analysed by a range of (immuno)histochemical and high‐resolution microscopy techniques. In vitro models of melanin granule uptake by human keratinocytes were attempted. Results: We propose a different fate for melanin in the human epidermis. Our evidence indicates that the bulk of melanin is inherited only by the nondifferentiating daughter cell postmitosis in progenitor keratinocytes via asymmetric organelle inheritance. Moreover, this preferred pattern of melanin distribution can switch to a symmetric or equal daughter cell inheritance mode under conditions of stress, including regeneration. Conclusions: In this preliminary report, we provide a plausible and histologically supported explanation for how human skin pigmentation is efficiently organized in the epidermis. Steady‐state epidermis pigmentation may involve much less redox‐sensitive melanogenesis than previously thought, and at least some premade melanin may be available for reuse. The epidermal melanin unit may be an excellent example with which to study organelle distribution via asymmetric or symmetric inheritance in response to microenvironment and tissue demands.